Carbon ceramics from plants: Graphitization of biomorphic matrixes - Iarmolenko, D.A.; Belyaev, A.E.; Kiselov, V.S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2016)
Properties of matrixes obtained from plants at various pyrolysis temperatures have been discussed. The article is devoted to graphitization of carbon matrixes obtained from plants. All stages of production, starting from preparation of the precursors up to high-temperature pyrolysis, have been considered together with some specific properties of matrixes at each stage. Previously unexplored new structural surface changes have been found. The use of potassium-doped wooden precursors showed the graphitization property of the matrix surfaces and allowed to form the matrix capillary wall coating with layers of crystalline graphite as well as graphene flakes and films with a low number of defects. New possibilities to apply these matrixes as examples of ultracapacitor, power unit filter electromagnetic interference and audio power amplifier antiresonance element have been discussed as well.